Addressing the Twin Threats: Combating Child Stunting and Poverty Among Indonesian Farmworker Families - Mardalena; Nida, Rahma; Kurnia, Tuti; Harunurrasyid (Jurnal Ekonomi Pembangunan, 2024)
This study identifies the underlying factors contributing to child stunting and poverty among Indonesian farmworker households. We use logistic regression and the Indonesian Family Life Survey to measure this study. The findings indicate that social and demographic factors significantly influence poverty among farming families. Families with more farming businesses and land ownership are less likely to be poor. However, there is no significant link between agricultural productivity and child stunting. Positive factors for child nutrition include exclusive breastfeeding for at least two years and a father's higher education level. In contrast, older maternal age and larger household size increase the likelihood of child stunting. The study highlights the importance of social and demographic factors in addressing poverty and child health in agricultural settings. Parental education and breastfeeding practices play crucial roles in preventing stunting. To address these issues, policies should focus on educating parents about the benefits of exclusive breastfeeding and early childhood nutrition. Supporting farming families by increasing agricultural productivity and land ownership is essential. Developing targeted nutritional programs for children in larger households and those with older mothers can help prevent stunting.